Data Mining : Introductory and Advanced Topics - Margaret H. Dunham (Pearson Education, 2006)
For undergraduate courses in Computer Science & Information Technology / MCA In this book the author provides the reader with a comprehensive coverage of data mining topics and algorithms. Data base perspective is maintained throughout the book which provides students with a focused discussion of algorithms, data structures, data types and complexity of algorithms and space. It also emphasizes the use of data mining concepts in real-world applications with large database components.